Comparison of Environment Impact between Conventional and Cold Chain Management System in Paprika Distribution Process - Putri, Eidelweijs A; Dowaki, Kiyoshi; Yudoko, Gatot; Koido, Kenji (School of Business and Management Institut Teknologi Bandung, 2012)
Pasir Langu village in Cisarua, West Java, is the largest central production area of paprika in Indonesia. On average, for every 200 kilograms of paprika produced, there is rejection amounting to 3 kilograms. This resulted in money loss for wholesalers and wastes. In one year, this amount can be approximately 11.7 million Indonesian rupiahs. Recently, paprika wholesalers in Pasir Langu village recently are developing cold chain management system to maintain quality of paprika so that number of rejection can be reduced. The objective of this study is to compare environmental impacts between conventional and cold chain management system in paprika distribution process using Life Cycle Assessment (LCA) methodology and propose Photovoltaic (PV) system in paprika distribution process. The result implies that the cold chain system produces more CO2 emission compared to conventional system. However, due to the promotion of PV system, the emission would be reduced. For future research, it is necessary to reduce CO2 emission from transportation process since this process is biggest contributor of CO2 emission at whole distribution process. Keywords: LCA, environmentally friendly distribution, paprika,cold chain, PV system